A low‐profile four‐element MIMO antenna array with new decoupling structures. Issue 10 (26th September 2018) - Zhou, Xiangyu; Zhai, Huiqing; Xi, Lei; Wei, Zichun; Ma, Shaobo; Zheng, Licheng
Abstract: A low‐profile four‐element multiple‐input multiple‐output (MIMO) antenna array with new decoupling structures is proposed in this letter. The presented MIMO antenna array contains four parts: dual‐polarized antennas, power dividers, the AMC surface, and the new decoupling structures. The height of the dual polarized antenna is 10 mm (0.08λ0, λ0 is the wavelength propagating in free space at 2.5GHz). Meanwhile, the proposed MIMO antenna array can offer an impedance band from 2.5 GHz to 2.7 GHz. The new decoupling structures can greatly improve the isolation of each port in the four‐element MIMO antenna array. Comparing with the tested results and the simulated results, they are relatively consistent.